Catalytic asymmetric umpolung reactions of imines - Wu, Yongwei; Hu, Lin; Li, Zhe; Deng, Li (Nature (London), 2015)
Imines conventionally act as electrophiles towards carbon nucleophiles in the synthesis of amines, but the range of amines could be much extended if the carbon atom of the imine could be rendered electron-rich to allow it to act as a nucleophile toward a carbon electrophile; such a reaction can be promoted by new phase-transfer catalysts, leading to highly efficient asymmetric reactions of imines with enals. Chital amine synthesis made simpler Imines, carbon–nitrogen double bonds, act as electrophiles towards carbon nucleophiles in the synthesis of amines, but the range of synthesizable amines could be greatly extended if the carbon atom of the imine could be rendered electron-rich to allow it to act as a nucleophile towards a carbon electrophile. Li Deng and colleagues have developed a procedure that achieves just that. They report the discovery and development of new chiral phase transfer catalysts that promote highly efficient asymmetric reactions of imines and enals. The reaction provides a conceptually new and practical approach towards the synthesis of chiral amino compounds. The carbon–nitrogen double bonds in imines are fundamentally important functional groups in organic chemistry. This is largely due to the fact that imines act as electrophiles towards carbon nucleophiles in reactions that form carbon–carbon bonds, thereby serving as one of the most widely used precursors for the formation of amines in both synthetic and biosynthetic settings 1 , 2 , 3 , 4 , 5 . If the carbon atom of the imine could be rendered electron-rich, the imine could react as a nucleophile instead of as an electrophile. Such a reversal in the electronic characteristics of the imine functionality would facilitate the development of new chemical transformations that convert imines into amines via carbon–carbon bond-forming reactions with carbon electrophiles, thereby creating new opportunities for the efficient synthesis of amines. The development of asymmetric umpolung reactions of imines (in which the imines act as nucleophiles) remains uncharted territory, in spite of the far-reaching impact such reactions would have in organic synthesis. Here we report the discovery and development of new chiral phase-transfer catalysts that promote the highly efficient asymmetric umpolung reactions of imines with the carbon electrophile enals. These catalysts mediate the deprotonation of imines and direct the 2-azaallyl anions thus formed to react with enals in a highly chemoselective, regioselective, diastereoselective and enantioselective fashion. The reaction tolerates a broad range of imines and enals, and can be carried out in high yield with as little as 0.01 mole per cent catalyst with a moisture- and air-tolerant operational protocol. These umpolung reactions provide a conceptually new and practical approach to chiral amino compounds.